الجهود الاتصالية لدى مصالح املاك الدولة و دورها في تعزيز الخدمة بالمرفق العام - محمد يحياوي; لخضر ميمون; د/ عطالله طريف (جامعة عمار ثليجي الاغواط, 2024)
الملخص يعرفالمرفقالعام (الجماعاتالمحلية) فيالجزائرتحولاتعديدةبينالتأسيسلمداخلنظريةوالبحثعلىافاقجديدةاخذتابعادهامنمجتمعالمعلوماتالتياصبحتفيهالمعلومةالمصدرالاساسيللميزةالتنافسية،الامرالذيفرضعليهاعادةالبحثللتموقعمنجديدضمنمايعرفبالاقتصادالرقمي،منخلالالعملعلىتحويلعديدالوظائفالاداريةللمرافقالعموميةمنشكلهاالتقليديإلىالالكترونيقصدتحقيقالنفعالعامكسمةاساسية،الباحثفيهذاالمجاليرىانمدخلالادارةالالكترونيةكمدخلجيدقصدتجويدالمرفقالعاموتعزيزقيمهمنالشفافيةوالديمقراطيةوالمساءلةالتيتبقىفاعليتهاحبيسةثقافةالتعاملالالكترونيمعهذهالاستراتيجيةالاتصالية. الكلماتالمفتاحية:تكنولوجياالمعلوماتوالاتصال – الادارةالالكترونية – الاتصالالعمومي – المرفقالعام–الشفافية Abstract: The General Facility (Local groups ) in Algeria defines several transformations between the establishment of theoretical approaches and the search for new horizons that have been taken away from the information society, in which knowledge has become the main source of competitive advantage, which necessitated the re-search of a new location within the so-called digital economy. The administrative functions of the public utilities from their traditional form to the electronic in order to achieve public benefit as a basic feature, the researcher in this field believes that the introduction of electronic administration as a good input in order to improve the public facility and enhance its values of transparency, democracy and accountability, which remains effective electronic culture to deal with this communication strategy Keywords: ICT, Electronic Governance, communication public, General Facility Principles, Transparency
دراسة على عينة من موظفي ولاية الاغواط